PENERAPAN MODEL PROBLEM BASED LEARNING PEMBELAJARAN MENULIS TEKS RESENSI BERORIENTASI ISI SISWA KELAS XI SMA PASUNDAN 7 BANDUNG - Endah Nur Sayidah; R. Panca Pertiwi Hidayati; Adi Rustandi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The research was motivated by the difficulty of student in writing text reviewer. It is characterized by the difficulty of students in developing written language, ideas and ideas in writing the contents of the reviewer’s text. The existence of a connection with the background described, that this study aims to determine the presence or absence of significant differences between students in learning by using the modelof problem based learning and discovery learning model of writing text reviews. This study uses a quatitative approach with quasi-experimental methods (quasi exsperimental). The design of this study is nonequivalent control group. Variables in this study are the independent variables in the form of problem based learning model and the dependent variable is the ability to write text reviewer. The population of this study were students of class XI in SMA Pasundan 7 Bandung. Based on the results of consideration, it was determined that class XI IPA-1 as an experimental class and class XI IPS-3 as a control class. Data collection techniques are tests and nontes (trials, observations, documentation and literature review). The results of the homogeneity test have been carried out data posttest both experimental and control classes declared equal or homogeneous distribution. Futher data were analyzed using non-parametric tests with Wilcoxon test and Mann-whitney U test. The results of the calculation of the test statistic of the Wilcoxon test in experimental and control classes both obtain Asymp. Sig. (2-tailed) 0.000 <0.05, it is concluded that there are differences in student learning outcomes writing text reviewer. In the mann-whitney U test results in the experimental class and the control class refers to the value of posttest obtained value of Asymp. Sig. (2-tailed) of 0.000 <0.05. It can be concluded that there is effectiveness on student learning outcomes in writing text skills experimental class reviewer using problem based learning model.